Текстовая функция модальной лексики (на материале прозаических произведений Чехова) - Waulina, Swietlana; Trofimowa, Irina (Acta Polono-Ruthenica, 2006)
The paper considers the function of the lexicon with modal meaning (verbs and predicative words), which expresses various shades of the „situational” modality (possibility, obligation, volition) and develops the subjective modality. The study of A.P. Chekhov’s stories The Duel, Rothschild’s Violin, The Teacher of Literature, The House with an Attic, Anna on the Neck, The Lady with the Dog, Ionych, and the novelette A Boring Story has led to the conclusion that the differentiation between the objective and subjective modality is but arbitrary.